COVID-19 Associated Myocarditis: A Monocentric Series of 33 Cases - Zaoui, Nassime; Boukabous, Amina; Bachir , Nadhir; Terki, Ali (Jordan Medical Journal, 2023)
Introduction: Myocarditis is defined by an inflammatory myocardial infiltrate with necrosis of non-ischemic origin in three forms: fulminant, acute and chronic. Diagnosis is guided by clinical presentation, ECG, echocardiography and biology, and confirmed by MRI and myocardial biopsy. The prognosis depends on clinical manifestations, echocardiographic features and serum troponin levels. Management is based on the treatment of heart failure (HF). For two years, the world has been experiencing a pandemic related to SARS-CoV2 that can affect the heart with ischemic or non-ischemic lesions (myocarditis, most often fulminant) whose treatment is non-specific. Trials with corticosteroids and immunosuppressant drugs have yielded discordant results. Objective: To describe the evolutionary modalities of COVID-19 associated myocarditis and identify factors of poor ejection fraction recovery under HF treatment. Method: This observational, retrospective, single-center study, in 2021, included patients with non-fulminant COVID-19 associated myocarditis suspected at echocardiography and biology and confirmed on MRI. Patients with previous HF and reduced left ventricular ejection fraction (LVEF) were excluded (n=06). Patients were divided into two groups according to LVEF three months later (LVEF>50% v. LVEF<50%) and compared to identify factors predicting a poor LVEF recovery. Results: 33 patients (19♂/14♀) aged between 30–61 years with acute non-fulminant COVID-19 associated myocarditis were included. All had ECG repolarization abnormalities. The mean LVEF at baseline was 44.3% +/- 6.3 (30–52%) with an average troponin level 480 times normal (20–2,100). Beta-blocker and RASB treatment was initiated in all patients, spironolactone (37.5 mg) in 13 patients with LVEF <40% and furosemide if congestive signs (17 patients/51.5%). Clinical, electrical, biological and echocardiographic monitoring was performed at one and three months. Eight patients developed uncomplicated pericardial effusion. A significant improvement in LVEF>50% was observed in 29 patients. One patient with LVEF of 38% presented with incessant ventricular tachyarrhythmia that necessitated an ICD. Three patients kept LVEF<50%. Sex, congestive signs, ECG and coronary angiogram abnormalities do not seem to influence the LVEF evolution (p at 0.62, 1.00, 1.00, 0.56, 0.50, and 0.23, respectively). Age >60 years, troponins >1,200 times normal, pericardial effusion and a combined criterion of the three seem to be a good predictor of poor LVEF evolution (p at 0.07, 0.02, 0.035 and 0.01, respectively). Discussion: The absence of fulminant forms in our series explains the absence of mortality at three months (>30% in the literature). Acute non-fulminant COVID-19 associated myocarditis has a good prognosis with LVEF recovery in 87.88%. The factors of poor LVEF recovery are the age >60 years, troponins >1,200 times normal, pericardial effusion, and the combined criterion of the three (p respectively at 0.07, 0.02, 0.035, 0.01). The routine prescription of corticosteroids in the COVID-19 protocol made it impossible to analyze its impact on COVID-19 associated myocarditis. Interpretation: Cardiac manifestations are not uncommon during COVID-19; they can be ischemic or non-ischemic. There is no specific therapy for non-fulminant COVID-19 associated myocarditis and the evolution seems favorable. Patients with predictive factors of poor progress should have longer follow-ups. Informed consent: All participants gave their informed consent to participate in this study and share the results